2012
DOI: 10.1002/lary.23268
|View full text |Cite
|
Sign up to set email alerts
|

Function‐preserving therapy for jugulotympanic paragangliomas: A retrospective analysis from 2000 to 2010

Abstract: With these high tumor control rates, consistent with the literature, function-preserving therapy for JTPs currently appears to offer the greatest benefit for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Immediate postoperative facial weakness is frequent, and long-term dysfunction is present in 14-33% of the cases (Briner et al 1999, Huy et al 2009). Hearing function either remains stable or deteriorates; it is subjectively improved in only 6-16% of the cases, while 39% may experience a deterioration (Glassock et al 1979, Gjuric et al 1996, Briner et al 1999, Kunzel et al 2012. Overall, up to 45.5% of the cases have some degree of hearing loss after surgery (Suarez et al 2013a).…”
Section: Jtpglsmentioning
confidence: 99%
“…Immediate postoperative facial weakness is frequent, and long-term dysfunction is present in 14-33% of the cases (Briner et al 1999, Huy et al 2009). Hearing function either remains stable or deteriorates; it is subjectively improved in only 6-16% of the cases, while 39% may experience a deterioration (Glassock et al 1979, Gjuric et al 1996, Briner et al 1999, Kunzel et al 2012. Overall, up to 45.5% of the cases have some degree of hearing loss after surgery (Suarez et al 2013a).…”
Section: Jtpglsmentioning
confidence: 99%
“…27,58,93 Whether SRS is used as a primary or salvage treatment modality is dictated by tumor location, the patient's preoperative status, and protocols at respective medical centers. Nonetheless, as a primary treatment modality, radiosurgery achieves local control rates comparable to those achieved with surgical approaches, while In normoxic conditions, the proline residues of hypoxia-inducible factor 1-a (HIF-1-a) are hydroxylated by prolyl hydroxylases, which use oxygen as a cofactor.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%
“…1A and C), 28,40,65,66 radiosurgery has become increasingly popular for residual tumors and cases not amenable to surgery. 27,58,93 Due to their highly vascular nature (Fig. 1B) and tendency to bleed intraoperatively, preoperative coil embolization has been used for SHN-PGs.…”
mentioning
confidence: 99%
“…In general, patients either maintain function of their cranial nerves or have improvement in their dysfunction after treatment but many of these studies included patients treated with multiple types of surgical and/or radiation treatment types. 6,12,13,2226 Our study demonstrated overall stability of cranial nerve function using single modality GKRS. Those with lower cranial neuropathies were rehabilitated well (i.e.…”
Section: Discussionmentioning
confidence: 53%